Serological survey for the presence of haemagglutination-inhibition to egg drop syndrome 76 virus in N. Greece - ΓΚΙΘΚΟΠΟΥΛΟΣ Π. Ρ.; ΠΑΣΧΑΛΕΡΗ-ΠΑΠΑΔΟΠΟΥΛΟΥ Ε.; .ΠΑΝΑΓΙΩΤΙΔΟΥ-ΜΑΜΑΛΟΥΚΑ Β. (Journal of the Hellenic Veterinary Medical Society, 2019)
For the investigation of EDS 76 in N. Greece, 465 serums and 301 eggs coming from 106 flocks of layers, 21 of broilers, 4 of turkeys and 4 of ducks were examined by HI test. From these, 72 serums and 33 eggs coming from 12 flocks of layers and I of ducks, contained antibodies against EDS 76 virus with titles higher than 1/8. The presence of antibodies against EDS 76 virus in correlation with problems in egg production and egg quality can give rise to conclusion that this syndrome is present in Greece.